1979
DOI: 10.3109/00365597909180015
|View full text |Cite
|
Sign up to set email alerts
|

Successful Kidney Transplantation in a Man with Dacron “Trouser” Prosthesis

Abstract: The case history of a male patient, 62 years old, in preterminal uremia at transplantation with a cadaveric kidney is described. Twelve years before the transplantation he was operated on because of an aortic aneurysm where the abdominal aorta and both iliac arteries were substituted with a Dacron prosthesis. The kidney was anastomosed to this vessel substitute and functioned excellently for more than five years and the patient was completely rehabilitated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In the majority of the instances in which sever aortoiliac disease is diagnosed intra-operatively during renal transplantation, anastomosis of renal artery to a vascular prosthetic graft posses a highly technical and unique challenge [2] [5]. Renal arterial anastomosis to a vascular prosthetic graft, was initially described by Sterioff et al in 1974 and later by Ahlmen et al Typically the case is not technically difficult except unless the iliac vein is scarred or fibrotic, in which case the renal vein can be anastomosed to inferior vena cava [1] [14] [15]. Coosemans et al reported on 16 renal transplant recipients in whom renal artery anastomosis was performed directly to a vascular prosthesis either simultaneously or after vascular surgery procedure for aortoiliac disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of the instances in which sever aortoiliac disease is diagnosed intra-operatively during renal transplantation, anastomosis of renal artery to a vascular prosthetic graft posses a highly technical and unique challenge [2] [5]. Renal arterial anastomosis to a vascular prosthetic graft, was initially described by Sterioff et al in 1974 and later by Ahlmen et al Typically the case is not technically difficult except unless the iliac vein is scarred or fibrotic, in which case the renal vein can be anastomosed to inferior vena cava [1] [14] [15]. Coosemans et al reported on 16 renal transplant recipients in whom renal artery anastomosis was performed directly to a vascular prosthesis either simultaneously or after vascular surgery procedure for aortoiliac disease.…”
Section: Discussionmentioning
confidence: 99%
“…In 1979, Ahlmen et al [13] reported the case of a 62-year-old man who benefited from a renal transplantation 12 years after an aorto-bi-iliac graft for aortic aneurysm. However, subsequent reports about grafting the renal artery to a vascular prosthesis during kidney transplantation have revealed conflicting results.…”
Section: Discussionmentioning
confidence: 99%